Pengaruh Pemberian Acidifier dengan Level Yang Berbeda Terhadap Konsumsi Pakan, Pertambahan Bobot Badan dan Konversi Pakan Pada Pejantan Ayam Kampung - Tajudin Tajudin; Sumarno Sumarno; Eka Fitasari (Jurnal Ilmiah Fillia Cendekia, 2021)
Acidifier is thought to be able to maintain pH balnce and change the pH to acid in the digestive organs of chickens. In addition, the acidifier can also maintain the balance of mocrobes in the digestive organ of livestock. Acidifier work by penetrating the bacterial cell wall, by maintaining or lowering the pH in the intestine. Pathogenic bacteria cannot tolerate a decrease in intestinal pH so that pathogenic bacteria must maintain intestinal pH by expending large enough energy so that over time the pathogenic bacteria die due to lack of energy, while non-pathogenic bacteria can tolerate changes in pH. acidifiers can be applied in feed and drinking water, as a supplement to help digest feed nutrients. From the above problem carried out scien tific research to test the acidifier as a supplement in feed using observational variables the performance of the original native chicken stud as an indicator. The purpose of this research is study the effect of giving an acidifier with different levels of feed consumption, addition weight gain, and feed conversion. Reset sites in the field laboratory Brawijaya University Sumbersekar in the year of 2019, with the method used is Complete Random Design (CRD) 4 treatment and 4 Replay. Research result show that giving acidifier no real effect (P>0,05) on feed consumtion, addition weight gain, and feed conversion. But gives positiveresult. It is recommended that the application of the acidifier level be increased to get more optimal result.